Study on Clinical Spectrum, Laboratory Profile and Outcome of Dengue Fever in Adults - Kabir, Muhammad Ashraful; Haque, Syed Didarul; Islam, Baishakhi; Imam, Hasan (Mediscope, 2021)
Background: Dengue infection is a major health burden, which can result in mild self-limited febrile illness to highly fatal haemorrhagic disease. Infection is caused by Dengue virus, which is transmitted by the Aedes aegypti mosquito. Objective: The aim of the study was to see the clinical spectrum, laboratory profile and outcome of dengue fever in adult. Methods: This prospective observational study was carried out on 75 patients in the department of medicine of Bangabandhu Sheikh Mujib Medical University, Dhaka from 11/07/2019 to 20/10/2019. All patients above 18 years with confirmed dengue, who were either hospitalized or managed as outdoor patients with NS1 (non-structural protein) antigen and/ or IgM dengue antibody positive were included in the study. The patients with concomitant malaria, typhoid and leptospirosis were excluded from the study. Detailed history and careful clinical examination were performed on each patient. Results: In this study, all patients (100%) had fever. Among them, 70 (93.3%) was suffering from headache, 66 (88.0%) myalgia, 32 (42.7%) abdominal pain, 30 (40.0%) conjuctival suffusion, 29 (38.7%) nausea/vomiting, 27 (36.0%) skin rashes, 14 (18.7%) pleural effusion, 13 (17.3%) ascites, 13 (17.3%) retro-orbital pain, 11 (14.7%) itching, 8 (10.7%) hepatomegaly, 7 (9.3%) splenomegaly. Death occurred in 3 (4.0%) patients. Rate of cure was 58 (77.3%) and ICU admission was required in 14 (18.7%), they were ultimately cured. Conclusion: Fever associated with headache and myalgia were the most common symptoms. Other common clinical features were abdominal pain, conjunctival suffusion, nausea/vomiting, skin rashes and pleural effusion. Regarding laboratory finding, platelet count has little role in management of dengue patients. Mediscope Vol. 8, No. 1: January 2021, Page 33-39